Maslow and relatedness: creating an interpersonal model of self-actualization - Hanley, Steven J.; Abell, Steven C. (2002)
Abraham Maslow proposed what has become an almost definitive model of self-actualization with his theory of a hierarchy of needs. It is based heavily on Western and individualistic ideals of personal growth that de-emphasize the importance of relatedness in self-actualization. Critiques of this Western notion of relatedness have come from feminist thinkers, existential philosophers, environmentalists, and more. In light of these critiques it seems prudent to rethink Maslow's hierarchy and his implicit assumptions about the health of autonomous living. Maslow is not dismissive of relatedness. His emphasis on relationships as vehicles for personal growth, those already highly self-actualized. The authors suggest here a modification to Maslow's hierarchy that more fully considers positive views of relatedness. This new interpersonal model of self-actualization emphasizes the importance of relatedness as the substance of individual growth at all levels of psychological development. Implications of this theory for parenting, family life, community living, and creative expression are also discussed. - Reproduced.
Keywords: Self esteem